Clinical Experience with the Implementation of Accurate Measurement of Blood Loss during Cesarean Delivery: Influences on Hemorrhage Recognition and Allogeneic Transfusion - Rubenstein, Andrew F.; Zamudio, Stacy; Al-Khan, Abdulla; Douglas, Claudia; Sledge, Sharon; Tully, Griffeth; Thurer, Robert L. (American Journal of Perinatology, 2018)
Objective This article compares hemorrhage recognition and transfusion using accurate, contemporaneous blood loss measurement versus visual estimation during cesarean deliveries.Study Design A retrospective cohort study using visually estimated blood loss (traditional, n = 2,025) versus estimates using a mobile application that photographs sponges and canisters and calculates their hemoglobin content (device, n = 756).Results Blood loss > 1,000 mL was recognized in 1.9% of traditional visual estimation patients, while measured blood loss of > 1,000 mL occurred in 8.2% of device patients (p < 0.0001). In both groups, this was accompanied by a greater decrease in transfusion-adjusted hemoglobin levels than occurred in patients without hemorrhage (p < 0.0001). Despite similar transfusion rates (1.6% in both groups), fewer red cell units were given to transfused patients in the device group (1.83 ± 0.58 versus 2.56 ± 1.68 units; p = 0.038). None of the patients in the device group received plasma or cryoprecipitate. Seven patients in the traditional group received these products (p = 0.088). Device use was associated with shorter hospital stays (4.0 ± 2.3 versus 4.4 ± 2.9 days; p = 0.0006).Conclusion The device identified hemorrhages more frequently than visual estimation. Device-detected hemorrhages appeared clinically relevant. Blood product transfusion was reduced possibly due to earlier recognition and treatment, although further studies are needed to verify the conclusion.
Keywords: cesarean delivery; blood loss; postpartum hemorrhage; quality improvement